Power Inequalities for the Numerical Radius of a Product of Two Operators in Hilbert Spaces - Dragomir, S. S. (Sarajevo Journal of Mathematics, 2024)
Some power inequalities for the numerical radius of a product of two operators in Hilbert spaces with applications for commutators and self-commutators are given. 2000 Mathematics Subject Classification. 47A12, 47A30, 47A63, 47B15